Engineering the Anthropocene: Scalable social networks and resilience building in human evolutionary timescales. (December 2017) - Fox, Tim; Pope, Matt; Ellis, Erle C
The Anthropocene represents the emergence of human societies as a 'great force of nature'. To understand and engage productively with this emergent global force, it is necessary to understand its origins, dynamics and structuring processes as the long-term evolutionary product of human niche construction, based on three key human characteristics: tool making, habitat construction and most importantly: social network engineering. The exceptional social capacities of behaviourally modern humans, constituting human ultrasociality, are expressed through the formation of increasingly complex and extensive social networks, enabling flexible and diverse group organisation, sociocultural niche construction, engineered adaptation and resilience building. The human drive towards optimising communication infrastructures and expanding social networks is the key human adaptation underpinning the emergence of the Anthropocene. Understanding the deep roots of human ultrasocial behaviour is essential to guiding contemporary societies towards more sustainable human–environment interactions in the Anthropocene present and future. We propose that socially networked engineered solutions will continue to be the prime driver of human resilience and adaptive capacity in the face of global environmental risks and societal challenges such as climate change, sea-level rise, localised extreme weather events and ecosystem degradation.